EPISTEMOLOGICAL INTEGRATION OF RATIONALISM AND SUFISM IN ISLAMIC EDUCATION: TOWARD A HOLISTIC LEARNING PARADIGM - Raharjo, Harmanto; Musthafa, Izzudin; Syafei, Isop; Rahmi, Aulia; Refani, Afda (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the relationship between rationalist and Sufi methods in the pursuit of truth and their implications for Islamic education. The discussion focuses on three aspects: (1) the epistemological characteristics of rationalist and Sufi methods, (2) the dialectical relationship between rationality and inspiration, and (3) their synthesis in holistic Islamic learning. The research applies a descriptive-analytical and comparative approach through library research, examining both classical works of Muslim scholars such as al-Farabi, Ibn Sina, al-Ghazali, and Ibn ‘Arabi, and relevant contemporary literature. The findings reveal that rationalism provides logical and systematic structures, while Sufism offers spiritual depth and transcendental meaning. Their dialectical interaction produces an epistemological synthesis with implications for integrative curricula, the transformation of teachers’ roles as mu‘allim and murabbī, and the formation of insān kāmil—an intelligent, wise, and spiritually grounded individual.